Investigation of LncRNAs expression in patients with hepatitis B virus - Cansu Önlen Güneri; Hamza Malik Okuyan; Gülay Gülbol Duran; Mehmet Demir (National Scientific Medical Center, 2022)
Aim: Patients infected with the hepatitis B virus (HBV) are at a higher risk of cirrhosis and hepatocellular carcinoma. Despite the recent advancement of antiviral therapy, many patients still cannot respond to existing therapies. Hence, to detect the changes in liver function earlier, non-invasive methods are needed. Long non-coding RNAs (lncRNAs) play important roles in essential biological process as well as human cancer. LncRNAs may be used as biomarkers in human diseases. Thus, in this study, we purposed to analyze the expression levels of lncRNAs (HOX transcript antisense RNA (HOTAIR), maternally expressed 3 (MEG-3), highly upregulated in liver cancer (HULC)) in patients with hepatitis B virus and healthy volunteers. Methods: We selected three lncRNAs as candidate lncRNAs based on their association with liver disease. Whole blood samples were collected from 40 patients with HBV and 48 healthy volunteers. The expression levels of all the samples were evaluated by quantitative real-time polymerase chain reaction (qRT-PCR). Statistical analysis was implemented using GraphPad Prism software. A p-value lower than 0.05 was statistically meaningful. Results: The expression levels of HOTAIR and HULC were remarkably upregulated in the plasma of the patients with HBV compared with healthy control (p<0.05). In contrast, no significant difference in MEG-3 expression levels was observed between groups. Conclusion: Our findings showed that the expression of HOTAIR and HULC in plasma might be new promising diagnostic and/or prognostic biomarkers for HBV.